I, or Not-I: (Self-)Consciousness in Sartrean and Buddhist Theory - Bartosiak, Katarzyna (Sensus Historiae, 2020)
The question of human specificity is accompanied by a subjective desire for auto-identification and self-knowledge. The ideas of Sartrean existentialism and early Buddhism (the Theravada tradition) presented in the paper are examples of non-egological conceptions, according to which human consciousness is deprived of a permanent self and is characterized by becoming rather than lasting. Sartre’s criticism of Husserl’s theory of transcendental ego and the Buddhist rejection of the Upanishads’ ātman are the starting points for two, often difficult in comparative studies, concepts of consciousness. The selflessness of consciousness is proven by the method of phenomenological description (Sartre), and Vipassana meditation (Buddhism). Both approaches allow the possibility of self-reflection and self-knowledge, but Sartrean consciousness is also self-consciousness, whilst Theravadian consciousness knows itself only through monodvara (the so-called “mind sense”). It is assumed in both theories that the empirical ego is a kind of false self-identification, as a result of which one lives in bad faith (Sartre) or in a state of ignorance, avijjā (Buddhism). The radical conversion, postulated in both theories, being an attainment of true self-knowledge, is also liberation from inauthenticity and ignorance.